Meloxicam efficacy and safety in treatment of pain syndromes of different localization according to domestic studies - O. A. Shavlovskaya; I. A. Bokova; N. I. Shavlovskiy (Неврология, нейропсихиатрия, психосоматика)
More than 500 million people worldwide suffer from osteoarthritis (OA). Neck and low back pain (LBP) is one of the most common reasons for visiting a general practitioner to receive primary medical care in different countries. The prevalence of chronic LBP varies from 4% to 20%, and increases linearly from the third decade to 60 years, and stabilizes in the seventh decade of life. According to the latest published clinical guidelines of the Russian Association for the Study of Pain, nonsteroidal anti-inflammatory drugs (NSAIDs) are used in minimally effective doses and a short course to relieve acute musculoskeletal pain. The ratio of the NSAIDs activity associated with cyclooxygenase (COX) – COX-1 / COX-2 – inhibition allows us to evaluate their potential toxicity. The smaller this value, the more selective the drug is against COX-2, and the less toxic it is. Meloxicam belongs to the predominantly selective COX-2 inhibitors. In the Russian market, meloxicam of domestic production - Amelotex® is widely prescribed. Several studies have shown the high efficacy and safety of meloxicam in the treatment of pain syndromes with different localizations (LBP, neck pain of vertebrogenic nature, OA, etc.), it can be recommended for elderly patients, patients with comorbid diseases such as arterial hypertension (AH), diabetes mellitus, gastrointestinal tract pathology. Meloxicam has a good efficacy and safety profile, a pronounced symptom-modifying effect.